Rangelia vitalii in a free-ranging maned wolf (Chrysocyon brachyurus) and co-infections. Issue 3 (December 2016) - Silveira, Julia Angélica Gonçalves; D'Elia, Mirella Lauria; de Oliveira Avelar, Isabela; de Almeida, Lara Ribeiro; dos Santos, Hudson Andrade; de Magalhães Soares, Danielle Ferreira; Ribeiro, Múcio Flávio Barbosa; dos Santos Lima, Walter; Ecco, Roselene
Abstract: An adult free-ranged female maned wolf was rescued from a periurban area subject to anthropogenic disturbances in the Minas Gerais, Brazil. The animal presented poor body condition and anemia. The clinical condition rapidly deteriorated culminating in dead and a necropsy was performed. The main gross lesions were marked anemia and blood content in the intestines accompanied by many types of parasites. The protozoa Rangelia vitalii was identified by histopathological analysis predominantly within the cytoplasm of endothelial cells of capillaries of the small intestine. The lymph nodes, spleen, bone marrow, dermis, lungs and kidney had similar protozoal forms but with mild or moderate intensity. Rangelia vitalii was confirmed by molecular assays. Hepatozoon sp., Leishmania sp., and Entamoeba spp., apparently not related to the clinical signs were also detected. The myriad parasites found in the intestines included nematodes ( Ancylostoma caninum, A . braziliensis, , Molineus sp., Pterygodermatites sp., and Trichuris sp.), cestodes ( Spirometra sp.) and (acanthocephalans. To our knowledge, R . vitalii was identified in C . brachyurus for the first time. These findings emphasize the fragility of Brazilian ecosystems, especially in disturbed areas, reinforcing the necessity of efforts to preserve these areas and wild carnivores, some of which are threatened with extinction, such as the maned wolf. Graphical abstract: Highlights: Rangelia vitalii was found in C hrysocyon brachyurus, especially in small intestine. Co-infections with other parasites were found, including some with zoonotic potential. Anemia was likely linked to R . vitalii, Ancylostoma spp and perhaps Spirometra. Health status of the near threatened maned wolf reflects anthropogenic disturbed of habitat.